2013
DOI: 10.1111/nph.12414
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic gene cluster in Lotus japonicus discloses novel enzyme functions and products in triterpene biosynthesis

Abstract: SummaryGenes for triterpene biosynthetic pathways exist as metabolic gene clusters in oat and Arabidopsis thaliana plants. We characterized the presence of an analogous gene cluster in the model legume Lotus japonicus.In the genomic regions flanking the oxidosqualene cyclase AMY2 gene, genes for two different classes of cytochrome P450 and a gene predicted to encode a reductase were identified. Functional characterization of the cluster genes was pursued by heterologous expression in Nicotiana benthamiana. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 85 publications
(125 reference statements)
1
74
0
1
Order By: Relevance
“…After the duplication event, loss of one duplicate gene is the most likely fate of newly duplicated genes (Lynch and Conery, 2000;Krokida et al, 2013), and the examples noted above represent the rare surviving cases of successful retention and functional diversification. Although multiple factors were noted previously to influence the retention of duplicate genes (Birchler and Veitia, 2012;, two questions regarding the duplicated enzyme may be quite relevant with regard to recruitment into specialized metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…After the duplication event, loss of one duplicate gene is the most likely fate of newly duplicated genes (Lynch and Conery, 2000;Krokida et al, 2013), and the examples noted above represent the rare surviving cases of successful retention and functional diversification. Although multiple factors were noted previously to influence the retention of duplicate genes (Birchler and Veitia, 2012;, two questions regarding the duplicated enzyme may be quite relevant with regard to recruitment into specialized metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their physical proximity on chromosome 2 (distance between the two genes of 14 Kb), CYP72A68-430 and CYP72A68-470 did not show similar expression patterns in leaves suggesting they did not act as a paralog gene cluster. On the contrary, a consistent expression in different tissues and developmental stages has been found for genes -an oxido-squalene cyclase and two CYP450s -belonging to a putative metabolic cluster involved in triterpene biosynthesis in Lotus japonicus (Krokida et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…In Arabidopsis, two gene clusters for the synthesis of novel triterpenes, thalianol and marneral, were identified (Field and Osbourn, 2008;Field et al, 2011). Gene cluster for the biosynthesis of a novel triterpene, dihydroluepol was also recently discovered in the model legume plant Lotus japonicus (Krokida et al, 2013). Most clusters have shown that the pair of terpene synthase and CYP are clustered and coordinately expressed across monocots and eudicots (Boutanaev et al, 2015).…”
Section: Regulations Of Ginsenosides Synthesismentioning
confidence: 98%